Working for the Union: British Trade Union Officers - Solomon, Norman A. (Relations industrielles / Industrial Relations, 1995)
The article reviews the book, "Working for the Union: British Trade Union Officers," by John Kelly and Edmund Heery.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Union leadership